The role of tungsten chemical state and boron on ammonia formation using N2–H2 radiofrequency discharges. (15th November 2021) - Antunes, R.; Marot, L.; Romero-Muñiz, C.; Steiner, R.; Meyer, E.
Abstract: This work aims at investigating the role of tungsten and boron surfaces on ammonia production with N2 –H2 radiofrequency plasmas at 3 Pa. The experiments combine the analysis of the reaction products and surface chemical environment using mass spectrometry and x-ray photoelectron spectroscopy (XPS). We show that NH3 is formed upon discharges of N2 or H2 after having exposed a tungsten (W) foil to H2 or N2, respectively. A higher amount of ammonia is formed for the N2 -then-H2 case, which we explain by the larger number of Eley–Rideal reaction channels for the formation of NH x (s) and the lower surface diffusion barrier for adsorbed hydrogen, calculated using the density functional theory (DFT). As a result, H(s) combines with N(s) or NH x (s) through Langmuir–Hinshelwood at a faster rate than N(s) combines with another N(s). The amount of NH3 formed with N2 –H2 discharges after conditioning the tungsten foil with H2, N2 or O2 was also investigated. We observed that this pre-conditioning plays no major role on the amount of NH3 detected with the residual gas analyser, albeit a small decrease was observed after H2 contamination. With DFT, the adsorption energies of H on WO3 and W are found to be similar, while the adsorption of N on WO3 is significantly weaker. The similar NH3 concentrations obtained with a clean and oxidized tungsten surface thus suggest that the adsorption of N does not limit the formation rate of ammonia. The production of NH3 on boron was evaluated as well. The boron surface reduced the amount of detected ammonia almost by half. On the one side, a significant amount of H2 was removed from the surface during the Ar cleaning that followed, which suggests a strong retention of hydrogen. On the other side, the XPS data reveals that nitrogen forms strong bonds with boron and impurities on the surface, regardless on whether hydrogen is previously present on the surface or in the plasma volume. The presence of hydrogen in the plasma volume, simultaneously with nitrogen or after nitrogen exposure, is nevertheless necessary for the formation of NH(s) and NH2 (s). No NH3 (s) was however detected with XPS. The increased retention of both hydrogen and nitrogen on the boron surface may thus hinder the formation of NH3 .